STRENGTHENING CHARACTER EDUCATION AS A RESPONSE TO THE CHALLENGES OF THE TIMES (Indonesian Journal of Education (INJOE), 2025)
The importance of strengthening character education is in response to the challenges of an increasingly complex and dynamic era. The acceleration of technology, globalisation and rapid social change expose society to a range of complex issues that require individuals with well-rounded intellectual, moral and emotional capacities. A character-focused approach to education not only strengthens students' competitiveness in the future world of work, but also promotes social cohesion in an increasingly diverse society. This study utilised an in-depth literature review. The results revealed that the successful implementation of character education requires close collaboration between the government, educational institutions, families and communities. With innovative and integrative teaching strategies and a holistic approach, character education can be organised in a more effective and sustainable way. The conclusion of this study confirms that strengthening character education is a must in the face of a modern era filled with uncertainty. It provides an understanding that investing in character education not only produces morally and emotionally better individuals, but also creates a more stable and productive society.